"Cow horn deformity" of distal ureters on intravenous urography in 8-year old child with urinary schistosomiasis: A case report - S M Ma′aji (Sahel Medical Journal, 2011)
Background: Urinary schistosomiasis or bilharziasis is an ancient disease found in many part the tropical world. It is the second most prevalent tropical disease after malaria, and a leading cause of morbidity in large areas of the world. Methods: A case report. Results: A case of ~Cow Horn deformity" of the distal ureters on intravenous urography in an 8- year old child with urinary schistosomiasis is reported.